(untitled) (Historia, 2021)
Clay, bone, ivory and stone figurines, constitute a much under-appreciated subject in History, Archaeology and Anthropology alike. Seemingly, these artefacts are considered to be too small to be recognised as sculpture, or too trivial to be included in material culture studies. Archaeological Figurines from Zimbabwe and Sculptured in Clay are two distinctive attempts at redressing the imbalance. Matenga investigates the possible meanings of a tradition of miniature clay sculpture, the florescence of which coincided with the rise of the Zimbabwe polity (900-1500 AD). The Schroda monograph, on the other hand, reveals to the public an unusual large cache of clay figurines from the wider Mapungubwe region, excavated almost thirty years ago on a site adjacent to the confluence of the Limpopo and the Shashe rivers.